2016
DOI: 10.1212/wnl.0000000000002324
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in HSPB8 causing a new phenotype of distal myopathy and motor neuropathy

Abstract: Objective: To report novel disease and pathology due to HSPB8 mutations in 2 families with autosomal dominant distal neuromuscular disease showing both myofibrillar and rimmed vacuolar myopathy together with neurogenic changes.Methods: We performed whole-exome sequencing (WES) in tandem with linkage analysis and candidate gene approach as well as targeted next-generation sequencing (tNGS) to identify causative mutations in 2 families with dominant rimmed vacuolar myopathy and a motor neuropathy. Pathogenic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
105
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 20 publications
6
105
0
1
Order By: Relevance
“…It is also interesting that a similar pattern of muscle and nerve involvement was recently reported in 2 families with distal weakness caused by mutation in the related protein encoded by HSPB8 . 8 …”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting that a similar pattern of muscle and nerve involvement was recently reported in 2 families with distal weakness caused by mutation in the related protein encoded by HSPB8 . 8 …”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, the researchers found clinically, electrophysiologically, and via neuroimagery, that "the p.R158H PDK3 mutation [findings from a second CMTX6 family] were similar to the axonal neuropathy reported in the [original] Australian family," even though the phenotype and genotype results indicated that the two families had mutations of a different haplotype [24]. Whole -exome sequencing research expanded HSPB8 mutations knowledge, which had previously only associated with either CMT type 2L or distal hereditary motor neuronopathy type IIa [25]. These researchers were also able to demonstrate that the eventual outcomes, when early neurogenic effects of HSPB8 mutations were present, were no longer limited to the aforementioned two diseases [25].…”
mentioning
confidence: 75%
“…The latter study's authors concluded that the finding "differs from demyelinating CMT1A patients and is similar to axonal CMT2A patients" [24]. Autosomal dominant distal neuromuscular disease research on HSPB8 mutations as the causal factor that resulted in myofibrillar aggregates and rimmed vacuolar myopathy combined with neurogenic changes revealed by MRI that the lower limb diffuse tissue alterations in the early disease stages eventually progressed in later stages to myopathy with a typical fatty deposition [45].…”
Section: Musculoskeletalmentioning
confidence: 91%
See 1 more Smart Citation
“…Because detailed long-term follow-up studies of patients with neuromuscular disorders are not frequently published, it is unclear if the phenotypic heterogeneity reported in the literature actually means the existence of distinct phenotypes, or if it, in some cases, reflects the accumulation of additional abnormalities in the same individual over time, as recently shown for the HSPB8 mutation p.K141E [3] causing a distal hereditary motor neuropathy and a myopathy. Based on our clinical experience with more than 60 patients, in some cases, over a 30-year time period, the phenotype caused by the p.G66V mutation in CHCHD10 is relatively uniform and recognizable, and the expansion of the phenotype to include typical CMT2 and ALS, although recently reported in the literature, has not been well substantiated.…”
mentioning
confidence: 99%